The Relationship between Behavioral Activation/Inhibition Systems (BAS/BIS) and Bullying/ Victimization Behaviors among Male Adolescents. - Sajjad Basharpoor; Parviz Molavi; Usha Barahmand; Seyed Amin Mousavi (Iranian Journal of Psychiatry, 2013)
Objective: This research was conducted to investigate the relationship between behavioral activation-inhibition systems and bullyingvictimization behaviors among adolescents. Method: This was a correlational and cross-sectional study. Two hundred and thirty school boys were selected randomly by multistage cluster sampling method, and participated in this research. This sample responded to a demographic questionnaire, the Revised Olweus Bully/ Victim questionnaire and the child version of behavioral inhibition/activation systems Scale in their classrooms and in the presence of the researcher. The collected data were analyzed by Pearson’s correlation and multiple regressions. Result: The results showed that bullying and victimization were correlated with both behavioral activation and behavioral inhibition systems (p<0.01). The results also showed that 18% of the variance in victimization and 31 % of the variance in bullying were explained by behavioral inhibition and behavioral activation systems respectively . Conclusion: The results of this study implied that BAS and BIS may play a role in the manifestation of bullying in adolescents.